2013
DOI: 10.2147/cia.s50939
|View full text |Cite
|
Sign up to set email alerts
|

Clinical investigation of transradial access for emergent percutaneous coronary intervention in patients with acute myocardial infarction

Abstract: BackgroundUse of intensive anticoagulation and antiplatelet therapy in acute myocardial infarction (AMI) potentially increases the risk of bleeding complications during percutaneous coronary intervention via the transfemoral route. Recently, the transradial access has been intensively employed as an alternative means for diagnostic and interventional procedures. A low incidence of vascular access site bleeding complications suggests that the transradial access is a safe alternative to the transfemoral techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However more catheters were utilised with the LRA when compared to the right. Overall the LRA approach was found to be as safe as the RRA approach [19][20][21][22].…”
Section: Rifle-steacs [9] 1001mentioning
confidence: 99%
“…However more catheters were utilised with the LRA when compared to the right. Overall the LRA approach was found to be as safe as the RRA approach [19][20][21][22].…”
Section: Rifle-steacs [9] 1001mentioning
confidence: 99%
“…Since then rapid advances in this technique and related devices have catapulted transradial intervention (TRI) to an internationally accepted benchmark and a clinically viable approach to PCIs [8][9][10][11]. A series of studies have demonstrated the superiority of TRI compared to conventional transfemoral intervention (TFI) in terms of reduced risk of adverse outcomes and shorter lengths of hos-pital stays [12][13][14][15][16][17][18][19][20][21][22][23]. A recent Scientific Statement from the American Heart Association highlights these advantages and recommends TRI even in patients with acute coronary syndrome (ACS) [24].…”
Section: Introductionmentioning
confidence: 99%